THE RELATIONSHIP BETWEEN THE VOLUME OF OUTPUT AND THE LEVEL OF UNEMPLOYMENT IN THE RURAL AREAS OF THE REGION - Marina Aleksandrovna VOLOKHOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The problem of unemployment for rural residents of municipalities in the region has become very relevant in recent years, as well as for all residents of Russia. In the current conditions, there was a massive reduction in jobs and depreciation of the labor force. Extremely low wages at vacant jobs, does not even ensure the simple reproduction of an employee The empirical method of grouping Sturges is used to determine 6 groups of districts depending on the level of unemployment. A methodical approach to planning the unemployment rate based on the interpretation of Okun's law is proposed. The paper estimated the empirical sensitivity coefficient and adjustment of the potential size of agricultural production per capita of the working population for all categories of farms (agricultural enterprises, peasant farms, personal subsidiary plots). Also, it aims to identify the dependence of changes in economic indicators based on the increase of employment level. It shows the possibility of reducing the unemployment rate о from 0.77 to 4.30 points with an increase in production by 7%; (taking into account the estimated sensitivity factor of 1.12).